New Era University constituents, and parents' perceptions on special adolescent students' (SAS) employability - Villanueva, Weena Moises (2005)
This study determined the perceptions of SPED teachers, parents, New Era administrators, employees, and concessionaire on Special Adolescent Students (SAS) employability. A survey-questionnaire was constructed and validated. An open-ended questionnaire was also included to elicit responses in terms of hiring and training SAS and the possible problems that may be encountered in hiring them. It was revealed that respondents have positive acceptance and approval of SAS' capability for employment and are willing to hire and train them in their workplaces. They regard academic, relational and self-direction, and occupational skills very much needed to prepare SAS for vocational works. Jobs that can be readily adapted to SAS at NEU are at the library, canteen, clerical, and maintenance jobs.